Diagnostic significance of secondary bacteremia in patients with COVID-19. Issue 4 (April 2023) - Nakagawara, Kensuke; Kamata, Hirofumi; Chubachi, Shotaro; Namkoong, Ho; Tanaka, Hiromu; Lee, Ho; Otake, Shiro; Fukushima, Takahiro; Kusumoto, Tatsuya; Morita, Atsuho; Azekawa, Shuhei; Watase, Mayuko; et al.
Abstract: Objectives: We investigated the occurrence of non-respiratory bacterial and fungal secondary infections, causative organisms, impact on clinical outcomes, and association between the secondary pathogens and mortality in hospitalized patients with coronavirus disease 2019 (COVID-19). Methods: This was a retrospective cohort study that included data from inpatients with COVID-19 from multiple centers participating in the Japan COVID-19 Taskforce (April 2020 to May 2021). We obtained demographic, epidemiological, and microbiological data throughout the course of hospitalization and analyzed the cases of COVID-19 complicated by non-respiratory bacterial infections. Results: Of the 1914 patients included, non-respiratory bacterial infections with COVID-19 were diagnosed in 81 patients (4.2%). Of these, 59 (3.1%) were secondary infections. Bacteremia was the most frequent bacterial infection, occurring in 33 cases (55.9%), followed by urinary tract infections in 16 cases (27.1%). Staphylococcus epidermidis was the most common causative organism of bacteremia. Patients with COVID-19 with non-respiratory secondary bacterial infections had significantly higher mortality, and a multivariate logistic regression analysis demonstrated that those with bacteremia (aOdds Ratio = 15.3 [5.97–39.1]) were at higher risk of death. Multivariate logistic regression analysis showed that age, male sex, use of steroids to treat COVID-19, and intensive care unit admission increased the risk for nosocomial bacteremia. Conclusions: Secondary bacteremia is an important complication that may lead to poor prognosis in cases with COVID-19. An appropriate medical management strategy must be established, especially for patients with concomitant predisposing factors.